Gestão de riscos na construção civil: mapeamento sistemático da literatura - Castro, Roberto Portela de; Carvalho, Michele Tereza Marques (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The globalized economic crisis, which began in 2008, affected the Civil Construction Industry. In this scenario of uncertainty, Risk Management (GR) becomes paramount for the success of the projects and for the survival of companies in the Architecture, Engineering, Construction, and Operation (AECO) area. The objective of this work is to show trends in GR in the publications in the last 5 years, identifying gaps, which point to the need for more research. In this sense, the Systematic Literature Mapping (MSL) was used as a method to identify and treat the information. As tendencies, were observed: the expressive amount of studies in developing countries; the representativeness of Corporate Risk Management; and maintaining the importance of the risks associated with the Triangle of Constraints (cost, term and quality). Already as gaps and opportunity for future studies, stand out: the management of opportunity; risk management throughout the supply chain; association with new methodologies; and the GR approach in the post-work phase. In this context, the main contribution was the gaps and opportunities for studies and future research.